2010
DOI: 10.1007/s12328-010-0160-2
|View full text |Cite
|
Sign up to set email alerts
|

A case report of undifferentiated carcinoma with osteoclast-like giant cells of the pancreas and literature review

Abstract: Osteoclast-like giant cell tumors rarely arise in the pancreas. Here we report the case of a 78-year-old woman who was diagnosed with a well-defined 3 cm multilocular mass in the pancreatic body by the use of ultrasonography, computed tomography and magnetic resonance imaging. The rim and the septa of the tumor were well enhanced. The distal pancreas was removed with the spleen and the peripancreatic lymph nodes. Macroscopically, the mass was composed predominantly of a multilocular cystic tumor filled with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…They are not present in normal tissues other than bones. Nevertheless, similar cells have been found in tumors of pancreas (Abid and Gnanajothy, 2019;Njoumi et al, 2014;Sah et al, 2015;Togawa et al, 2010;Bauditz et al, 2006), liver (Bauditz et al, 2006;Dioscoridi et al, 2015;Ikeda et al, 2003;Kuwano et al, 1984;Rosai, 1990), skin (Goel et al, 2011;Al-Brahim and Salama, 2005;Jiménez-Heffernan et al, 2018;Houang et al, 2015), lung (Nakahashi et al, 1987;Matsukuma et al, 2014;Lindholm et al, 2019;Kong et al, 2015;Dahm, 2017), breast (Stewart and Mutch, 1991;Agnantis and Rosen, 1979;Fadare and Gill, 2009;Ginter et al, 2015;Ohashi et al, 2018), and in many other tumors. Osteoid and bone formation was found in different cancers, such as breast cancer and melanoma (Hoorweg et al, 1997;Dekkers et al, 2019) These tumors can be considered as degenerated or more severely defected forms of teratomas/teratocarcinomas.…”
Section: Tumor Phenotypic Heterogeneitymentioning
confidence: 58%
“…They are not present in normal tissues other than bones. Nevertheless, similar cells have been found in tumors of pancreas (Abid and Gnanajothy, 2019;Njoumi et al, 2014;Sah et al, 2015;Togawa et al, 2010;Bauditz et al, 2006), liver (Bauditz et al, 2006;Dioscoridi et al, 2015;Ikeda et al, 2003;Kuwano et al, 1984;Rosai, 1990), skin (Goel et al, 2011;Al-Brahim and Salama, 2005;Jiménez-Heffernan et al, 2018;Houang et al, 2015), lung (Nakahashi et al, 1987;Matsukuma et al, 2014;Lindholm et al, 2019;Kong et al, 2015;Dahm, 2017), breast (Stewart and Mutch, 1991;Agnantis and Rosen, 1979;Fadare and Gill, 2009;Ginter et al, 2015;Ohashi et al, 2018), and in many other tumors. Osteoid and bone formation was found in different cancers, such as breast cancer and melanoma (Hoorweg et al, 1997;Dekkers et al, 2019) These tumors can be considered as degenerated or more severely defected forms of teratomas/teratocarcinomas.…”
Section: Tumor Phenotypic Heterogeneitymentioning
confidence: 58%
“…Bile duct dilatation, pancreatic duct dilatation and necrotic areas are common findings (54,55). Calcification (56), hemorrhage (56,57), and venous tumor thrombus (57) have also been described. At abdominal MRI UC-OGC usually presents a low to dark signal intensity on T1-and T2-weighted images.…”
Section: Diagnosismentioning
confidence: 99%
“…In addition, it has been reported that UCP may arise from cystic neoplasms, such as mucinous cystic neoplasms (MCNs) and intraductal papillary mucinous neoplasms (IPMNs) . However, differential diagnosis of UCP versus UCP arising from cystic neoplasm may be difficult . Furthermore, intraductal tumour growth in the MPD may be mischaracterized as solid intraductal tumours such as IPMN without mucin‐hypersecretion, intraductal tubulopapillary neoplasm (ITPN), and intraductal and papillary variant of acinar cell carcinoma .…”
Section: Discussionmentioning
confidence: 99%